Daily Energy Expenditure and Its Relation to Health Care Costs in Patients Undergoing Ambulatory Electrocardiographic Monitoring - George, Jason; Abdulla, Rami Khoury; Yeow, Raymond; Aggarwal, Anshul; Boura, Judith; Wegner, James; Franklin, Barry A. (The American journal of cardiology, 2017)
Our increasingly sedentary lifestyle is associated with a heightened risk of obesity, diabetes, heart disease, and cardiovascular mortality. Using the recently developed heart rate index formula in 843 patients (mean ± SD age 62.3 ± 15.7 years) who underwent 24-hour ambulatory electrocardiographic (ECG) monitoring, we estimated average and peak daily energy expenditure, expressed as metabolic equivalents (METs), and related these data to subsequent hospital encounters and health care costs. In this cohort, estimated daily average and peak METs were 1.7 ± 0.7 and 5.5 ± 2.1, respectively. Patients who achieved daily bouts of peak energy expenditure ≥5 METs had fewer hospital encounters (p = 0.006) and median health care costs that were nearly 50% lower (p <0.001) than their counterparts who attained <5 METs. In patients whose body mass index was ≥30 kg/m2, there were significant differences in health care costs depending on whether they achieved <5 or ≥5 METs estimated by ambulatory ECG monitoring (p = 0.005). Interestingly, patients who achieved ≥5 METs had lower and no significant difference in their health care costs, regardless of their body mass index (p = 0.46). Patients with previous percutaneous coronary intervention who achieved ≥5 METs had lower health care costs (p = 0.044) and fewer hospital encounters (p = 0.004) than those who achieved <5 METs. In conclusion, average and peak daily energy expenditures estimated from ambulatory ECG monitoring may provide useful information regarding health care utilization in patients with and without previous percutaneous coronary intervention, irrespective of body habitus. Our findings are the first to link lower intensities of peak daily energy expenditure, estimated from ambulatory ECG monitoring, with increased health care utilization.